LOADING AND UNLOADING LABOR PERFORMANCE AS A MEDIATION OF VARIABLES OF WORK MOTIVATION, WORK COMPETENCE AND WORK BEHAVIOR THAT IMPACTS WELL-BEING LOADING AND UNLOADING LABOR - Aswanti Setyawati; Yosi Pahala; Primadi Candra Susanto (ABNUS Publisher, 2022)
The purpose of the study was to find the influence between variables with quantitative research methods with analytical tools to search for data using SEM PLS, the results of the study stated The value of the R square Adjusted equation X2 = 0.634*X1 + e from the table above 0.396 indicates that 39.6% of the variance X2 can be explained by the change in the variable X1, while the other 60.4% is due to other factors outside the model. From the results of each variable, it has a positive effect and the remaining results will later be continued by other researchers for other variables.